2007
DOI: 10.1590/s0102-09352007000500008
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic granulomas in canine visceral leishmaniasis and clinical status

Abstract: The histopathological description of intralobular hepatic granulomas in animals with a defined clinical status (asymptomatic, oligosymptomatic and symptomatic animals) was reported. Seventy-one mongrel dogs naturally infected with Leishmania chagasi were obtained from two Brazilian endemic areas: João Pessoa, PB and Belo Horizonte, MG. The hepatic parasite load was determined and compared to granuloma formation. Liver fragments from all infected animals showed remarkable leishmaniotic granulomatous inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…In the course of leishmaniasis, granulomas are associated with the resolution and clearance of the liver infection in the murine model (LoeuILLet et al, 2016) and allow local concentration of inflammatory cytokines that activate the leishmanicidal mechanisms of Kupffer cells (SRIVaStaVa et al, 2016), which may explain the higher IFN-γ median found in samples with granuloma. although, there are other causes for hemosiderin presence, this finding in the liver was previously reported in CVL (SaNt'aNa et al, 2007), and possibly the low nitric oxide production in symptomatic animals is associated with higher rates of iron deposition on tissue (SouZa et al, 2014), which corroborates our results. Moreover, evidence suggested that symptomatic dogs present increased lipid peroxidation and tissue iron deposition associated with enhanced levels of antioxidant enzymes; and therefore, these changes in the oxidative balance may aggravate the pathological process in CVL (SouZa et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the course of leishmaniasis, granulomas are associated with the resolution and clearance of the liver infection in the murine model (LoeuILLet et al, 2016) and allow local concentration of inflammatory cytokines that activate the leishmanicidal mechanisms of Kupffer cells (SRIVaStaVa et al, 2016), which may explain the higher IFN-γ median found in samples with granuloma. although, there are other causes for hemosiderin presence, this finding in the liver was previously reported in CVL (SaNt'aNa et al, 2007), and possibly the low nitric oxide production in symptomatic animals is associated with higher rates of iron deposition on tissue (SouZa et al, 2014), which corroborates our results. Moreover, evidence suggested that symptomatic dogs present increased lipid peroxidation and tissue iron deposition associated with enhanced levels of antioxidant enzymes; and therefore, these changes in the oxidative balance may aggravate the pathological process in CVL (SouZa et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…In this sense, BoRJa et al (2016) also reported no significant association between the clinical manifestations and parasite load in the spleen of dogs naturally infected with L. infantum. Regarding hepatic analyses, Sant'ana et al (2007) also did not find any significant differences between the parasite load in liver and canine clinical status, similarly to the results obtained for the liver samples in this study. These findings are still in accordance with our recent previous results on lymph node parasite load and clinical evaluation in dogs, which presented no significant difference (de VaSCoNCeLoS et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Resolution of disease in this organ is associated with granuloma formation, which is one of the key features of hepatic resistance. The resolution of the infection in the liver (in humans, dogs and mouse models) is attributed to the development of a Th1-dominated granulomatous response, that is able to restrain the parasite dissemination and is characterized by high IFN-γ, IL-12 and TNF-α production through CD4 + T cells (Sant'Ana et al ., 2007; Melo et al ., 2009; Kaye and Beattie, 2016). IL-12 has been described, as an essential cytokine in the development of protective immunity against Leishmania.…”
Section: Discussionmentioning
confidence: 99%
“…Livers of asymptomatic dogs showed an effective immunity with well-organized granulomas able to isolate and restrain parasite spreading, in an immune environment of activated effector T cells, dendritic cells (DCs) and central memory cells. In contrast, liver of symptomatic dogs showed a non-organized and ineffective infiltrate of T cells and heavily parasitized KCs (Sant'Ana et al ., 2007; Murray, 2008). Despite these local responses, Leishmania is able to disseminate and produce symptomatic VL.…”
Section: Introductionmentioning
confidence: 99%